Risperidone-Induced Obesity in Children and Adolescents With Autism Spectrum Disorder: Genetic and Clinical Risk Factors - Vanwong, Natchaya; Ngamsamut, Nattawat; Nuntamool, Nopphadol; Hongkaew, Yaowaluck; Sukprasong, Rattanaporn; Puangpetch, Apichaya; Limsila, Penkhae; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2020)
Aims: Obesity is a significant problem for patients taking atypical antipsychotics. There were two aims of our study. The first aim was to compare the prevalence of overweight and obesity between children and adolescents with autism spectrum disorder (ASD) treated with risperidone with the general pediatric population. The second aim was to investigate the association of the HTR2C –759C>T, ABCB1 1236C>T, ABCB1 2677G>T/A, and ABCB1 3435C>T polymorphisms with risperidone-induced overweight and obesity in children and adolescents with ASD. Methods: Body weight and height were measured in 134 subjects. Overweight and obesity in children and adolescents were classified using the International Obesity Task Force (IOTF) criteria. Genotyping was performed by TaqMan real-time polymerase chain reaction (PCR). Results: Our study found that the prevalence of overweight and obesity was significantly higher in children and adolescents with ASD treated with risperidone compared with healthy individuals (p = 0.01 and p = 0.002). The genetic polymorphisms of HTR2C –759C>T, ABCB1 1236C>T, ABCB1 2677G>T/A, and ABCB1 3435C>T were not associated with overweight/obesity in children and adolescents with ASD treated with risperidone after adjustment for multiple comparisons by the method of Bonferroni. Additionally, haplotype analysis revealed that there was no significant association between ABCB1 1236T-2677T/A-3435T haplotype and overweight/obesity. In multivariate logistic regression, after adjustment by the Bonferroni correction, there was only the duration of risperidone treatment that was significantly associated with overweight/obesity in children and adolescents with ASD. Conclusions: The findings suggest that children and adolescents with ASD treated with risperidone are at a higher risk of obesity, especially patients with extended treatment with risperidone. For the pharmacogenetic factors, –759C>T polymorphism of HTR2C gene and 1236C>T, 2677G>T/A, and 3435C>T polymorphisms of ABCB1 gene were not likely to be associated with the susceptibility to overweight/obesity in children and adolescents treated with risperidone. Due to the small sample size, further studies with a larger independent group are needed to confirm these findings.